The Legal Aspect of Consumers' Protection from Pop-Up Advertisements in Indonesia - Prastyanti, Rina Arum; Yafi, Eiad; Wardiono, Kelik; Budiono, Arief (University of Jember, 2021)
Pop-up advertisements have become prevalent on websites. When users click on the banner, they navigate a separate window; banner and pop-up advertisements contain attractive audio-visual and animated graphics. This intrusive advertising has not explicitly regulated Indonesia's current legislation, including Electronic Transaction and Information Law 11/2008 (ITE Law). Also, it is exempted in the Indonesian Pariwara Ethics, guidelines for advertising ethics and procedure in Indonesia. This study aimed to revisit consumers’ protection toward pop-up advertisements in Indonesia, with two main discussions. First, it discussed online consumers' perceptions of pop-up advertisements and the classification of their responses. Second, it enquired to what extent the legal and ethics protection for online consumers in Indonesia. By using empirical legal research, this study concluded that the ITE Law prohibits anyone from spreading online information with content that violates immorality and gambling, as it often contains in pop-up advertisements. Through the lens of business ethics, pop-up advertisements are new media and they should not be installed in such a way as to interfere with the freedom of internet users, given that pop-up advertisements do not reflect the ethics of honesty, trust, and advice in business. KEYWORDS: Consumers’ Protection, Online Advertisements, Business Ethics.